Real time handling system to enhance the productivity based on the layout improvement - Al Hazza, Muataz Hazza Faizi; Any Nabila, Bt Abu Bakar; Taha, Assem Hatem; Adesta, Erry Yulian Triblas (Praise Worthy Prize, 2016)
Factory layout is one of the key factors that may increase the productivity and the production rate in industrial organizations. A suitable layout with online tracking system for the movement of final product, work in progress and inventory locations will enhance the material handling system. However, the development of new technologies such as Automated Guided Vehicle (AGV) system and Radio Frequency Identification (RFID) may help in improving the utilization of factory facilities. The aim of this research is to analyze the effect of using (AGV) system and (RFID) technology to track and trace the flow of more than one type of products in order to enhance and improve the utilization of the production line. In this research, the integration between two advanced technologies, AGV system and RFID technology, has been simulated using Delmia Quest software as one of the effective tools for the simulation of discrete events. The simulation was conducted using the AGV as handling system and the RFID as tracking system for each individual product. The results show the of the production rate and the utilization of all the machines. As a result, the idle time was decreased. In conclusion, both the AGV and RFID both have their own role to increase the productivity of the factory layout. Finally, this project will be tested by some modelling and simulation with the Delmia QUEST software.